Transformasi Pendidikan Bahasa Indonesia dalam Menghadapi Era Revolusi Industri 5.0 - Putri Nadiarahma; Hindun Hindun (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to describe Indonesian language education as a solution to the development of the times, the teaching of Indonesian language education is not just an idea or theory. However, the implementation of Indonesian language education is a tool for students to be able to survive Indonesian language problems. The method used in this study was three literature reviews. Data in this study were obtained from reading book references, journal articles and seminar processing. The results of this study are (1) Transformation on Indonesian Language Teaching, (2) Transformation of Indonesian Language Education on 21st Century Skills, (3) Transformation in Character Values in Indonesian Language Education, (4) Transformation in Indonesian Language Education Curriculum, and (5) Transformation of Indonesian Language Education in Exposing the Era of the 5.0 Industrial Revolution.